Influence Of Training Volume On Heart Rate Variability In Race-walking Athletes - Belaid , Ferhat; Nabila, Touabti; Mokhtar , Boufaroua; Fayçal, Rebaine (Journal of Sport Science Technology and Physical Activities, 2025)
The aim of this study is to identify the interactions between weekly training loads, intensity zones, the Rating of Perceived Exertion (RPE), and Heart Rate Variability (HRV). To this end, a longitudinal monitoring method was applied to six elite racewalking athletes, selected for their high performance level. Data collection involved daily HRV measurements (including RMSSD, HF/LF Ratio, and their logarithmic transformations) taken in both supine and standing positions, along with RPE assessed after each training session. The data were analyzed using both linear and nonlinear statistical models. The results indicate that moderate training volumes (approximately 140 km/week) and a predominance of Zone_2 intensity favor enhanced autonomic recovery, while higher volumes and Zone_3 intensity are associated with increased physiological stress. Based on these findings, the study recommends regulating training loads and using HRV and RPE together as monitoring tools to individualize training and prevent overreaching.